Ser ou não ser (de santo)?: aspectos do campo religioso afro-brasileiro na peça teatral Balbina de Iansã, de Plínio Marcos - Martins, Gilberto Figueiredo [UNESP] (My University, 2010)
To be or not to be (of candomblé)? – aspects of Afro-Brazilian religious field in the theater play Balbina de Iansã, by Plínio Marcos. In 1970, the playwright born in Santos-SP Plínio Marcos writes and directs the spectacle Balbina de Iansã, an adaptation (in form of a musical) from Romeo and Juliet, by Shakespeare. The action happens in a candomblé yard, managed authoritatively by a Mãe-de Santo, who tries to prevent the young protagonist couple’s love. This study analyzes the representation of some rites and principles of Afro-Brazilian religion in the play, especially concerning the critique of the relations of power that exist in the yards of São Paulo.

Ser ou não ser (de santo)? – aspectos do campo religioso afro-brasileiro na peça teatral Balbina de Iansã, de Plínio Marcos. Em 1970, o dramaturgo santista Plínio Marcos escreve e dirige o espetáculo Balbina de Iansã, uma adaptação (em forma de musical) de Romeu e Julieta, de Shakespeare. A ação ocorre em um terreiro de candomblé, dirigido autoritariamente por uma mãe-de-santo, que tenta impedir o amor do jovem casal protagonista. O ensaio analisa a representação de alguns ritos e princípios da religião afro-brasileira na peça, com destaque para a crítica às relações de poder vigentes nos terreiros paulistas.
To be or not to be (of candomble)?: aspects of afro-brazilian religious field in the theater play Balbina de Iansã, by Plinio Marcos
Keywords: Brazilian dramaturgy; Plínio Marcos; AfroBrazilian religions; Intertextuality; Dramaturgia brasileira; Plínio Marcos; Religiões afro-brasileiras; Intertextualidade